Evaluation of the soil moisture model with data assimilation by the triple collocation method - Kozhushko, Olena; Boiko, Mykhailo; Kovbasa, Mykola; Martyniuk, Petro; Stepanchenko, Olha; Uvarov, Mykola (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
This paper deals with a nonlinear soil moisture transport problem, solved with addition of satellite observed soil moisture. The satellite data are assimilated into the model using Newtonian nudging method. Evaluation is done by the triple collocation method, which involves three independent data sources: model results, ground stations and ERA5 climatic data. The results testify that model results are nearly as accurate as the ground station measurements.